Protective Effect of Captopril against Doxorubicin-Induced Oxidative Stress in Isolated Rat Liver Mitochondria: Effect of captopril on doxorubicin toxicity - Hossein Niknahad,; Alireza Taghdiri,; Afshin Mohammadi-Bardbori,; Abbas Rezaeian Mehrabadi, (Iranian Journal of Pharmaceutical Sciences, 2010)
Doxorubicin (DOX) is an anthracycline antibiotic that has been used for a long time in therapy of an array of human malignancies either alone or in combination with other cytotoxic agents. The dose-dependent cardiotoxicity of DOX significantly limits its anticancer efficacies. Oxidative stress caused by enhanced production of reactive oxygen species is an important contributor to DOX mitochondrial toxicity. In the present study, DOX produced a significant elevation in TBARS, which is an indicator of lipid peroxidation, and significantly inhibited the activity of superoxide dismutase in rat liver mitochondria. Mitochondrial GSH dramatically decreased while GSSG was increased upon treatment of mitochondria by DOX. Co-treatment with captopril significantly reduced the lipid peroxidation in mitochondria and prevented the inhibition of superoxide dismutase activity induced by DOX. Captopril also significantly increased the level of GSH in DOX-treated mitochondria. These results, therefore, suggest that captopril acts as an antioxidant and can protect the mitochondria against DOX-induced oxidative stress. This effect appears to be due to the sulfhydryl groups of captopril which may act as antioxidant or scavenger of reactive oxygen species.